2020
DOI: 10.1016/j.jpeds.2020.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Dissatisfaction among Pediatric Patients with Inflammatory Bowel Disease

Abstract: Objectives To determine risk factors for body image dissatisfaction among pediatric patients with inflammatory bowel disease (IBD). Study design We performed a cross-sectional study of children aged 9-18 years in the IBD Partners Kids & Teens cohort. Participants completed surveys including demographics, disease characteristics and activity indices, and psychosocial outcomes measured by IMPACT-III questionnaires. We defined body image dissatisfaction if participants answered "I look awful" or "I look bad." Biv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…First, the percentage of youth with clinically elevated levels of depressive symptoms and the concomitant psychosocial challenges observed in the present study emphasize the need for routine screening of social and emotional difficulties during IBD clinic visits [26,27]. Importantly, because female participants in our sample were more likely to endorse both body image concerns and depressive symptoms, it is important that medical and behavioral health professionals be made aware of the potential unique body image-related emotional challenges faced by female youth with IBD [11,12]. Even though age was not related to the primary variables, it will be important for future research to examine ways to best implement body image and depression interventions across age groups.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…First, the percentage of youth with clinically elevated levels of depressive symptoms and the concomitant psychosocial challenges observed in the present study emphasize the need for routine screening of social and emotional difficulties during IBD clinic visits [26,27]. Importantly, because female participants in our sample were more likely to endorse both body image concerns and depressive symptoms, it is important that medical and behavioral health professionals be made aware of the potential unique body image-related emotional challenges faced by female youth with IBD [11,12]. Even though age was not related to the primary variables, it will be important for future research to examine ways to best implement body image and depression interventions across age groups.…”
Section: Discussionmentioning
confidence: 98%
“…Zero-order correlations and t -tests were also conducted to determine potential demographic and disease covariates. Previous research has indicated that both BMI and steroid medications can impact body image dissatisfaction [11]; therefore, we included BMI and steroid medication status as covariates in the primary analyses. Additional preliminarily correlation analyses examined the zero-order associations among the key study variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with poorly controlled IBD resulting in stunted growth or delayed puberty tended to have lower self-esteem than their healthy peers. 6 The physical, social and emotional well-being of children with IBD are often adversely impacted in addition to clinical symptoms and functional limitations. [7][8][9] It has become essential to assess the potential impact of chronic, relapsing disease on the overall wellbeing and the health-related quality of life (HRQoL) in these children.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…In addition to requiring the care of a pediatric gastroenterologist, they also require ongoing preventative care from a primary care provider, and frequently require consultations with other pediatric subspecialists to address comorbid conditions and complications of IBD therapies [4]. In the psychosocial sphere, patients with IBD are at increased risk for mood and body image concerns, as well as academic, social and family distress [5][6][7][8][9][10][11]. For this reason, a multidisciplinary team including nurses, dietitians, social workers, and psychology providers is essential to care for the entire patient and his or her family.…”
Section: Introductionmentioning
confidence: 99%